(untitled) (International Journal of Medical and Surgical Sciences, 2014)
Performing a surgical procedure of the small intestine, whether it is a scheduled elective or an emergency event, may be associated with the occurrence of disorders of diverse etiology; either as a result of prior illness, the onset of systemic pathology associated with the surgical event or complications related to the surgery itself. The development of morbidity in patients undergoing intestinal surgery has been outlined in this article on medical and surgical complications. These will be discussed based on clinical manifestations, potential risk factors associated with their occurrence and certain preventive measures.